Preparation of 2-phenyl-9-diethylaminoethylimidazo[1,2-α]benzimidazole dinitrate tablets and development of quality control methods - A. M. Domanina; M. V. Chernikov; I. P. Remezova; E. F. Stepanova; A. M. Shevchenko; A. V. Morozov (Разработка и регистрация лекарственных средств)
Introduction. Currently, for the treatment of gastric ulcer, drugs with a combined effect are used. To eliminate possible side effects of the drugs used, the search for new molecules to create more effective and safe histamine H2 receptors continues. As a possible solution to these problems, we investigated the substance dinitrate of 2-phenyl-9-diethylaminoethylimidazo[1,2-α]benzimidazole (DFDB).Aim. The aim of this study was to obtain 2-phenyl-9-diethylaminoethylimidazo[1,2-α]benzimidazole dinitrate tablets and develop methods for quality control.Materials and methods. The object of study was tablets based on the substance DF DB. The physicochemical and technological properties of the tablet dosage form were studied. Pharmaco-technological and physico-chemical indicators were determined according to the methods of the State Pharmacopoeia of the XIV edition. Identification and quantitative determination of DFDB in tablets was performed by HPLC.Results and discussion. Based on the physico-chemical properties and determination of the main technological indicators of DFDB, an optimal tableting technology has been developed. The optimal composition of tablets has been developed. Identification of tablets is proposed to be carried out using HPLC in comparison with the standard sample of DFDB. Related impurities, according to the data obtained, do not exceed 0.1 %. We found that the tablets do not have an antimicrobial effect. The analyzed tablets correspond to category 3A. The content of DFDB should be from 95 to 105 % of the declared amount in one tablet. During the analysis, we conducted biopharmaceutical and technological studies of the finished dosage form during storage under the conditions of long-term stability testing in polymer cans with screw-on lids. It is shown that the selected composition of excipients and the production technology ensure the stability of the finished dosage form for two years of storage under the observed conditions. To select the tableting technology, the main technological properties of the DFDB substance are analyzed. The choice of excipients and the composition of the film coating was carried out.Conclusion. The technology is developed and standardization of tablets based on the substance DFDB is proposed.